The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s00586-002-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of combined IGF-I and TGF-β1 application in a sheep cervical spine fusion model

Abstract: Combined IGF-I and TGF-β1 application by a poly-(D,Llactide) (PDLLA) coated interbody cage has proven to promote spine fusion. The purpose of this study was to determine whether there is a dosedependent effect of combined IGF-I and TGF-β1 application on intervertebral bone matrix formation in a sheep cervical spine fusion model. Thirty-two sheep underwent C3/4 discectomy and fusion. Stabilisation was performed using a titanium cage coated with a PDLLA carrier including no growth factors in group 1 (n=8), 75 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Additionally, Kandziora et al[45] investigated the effects of IGF-1/TGF-beta-1 in a sheep anterolateral (C3-C4) interbody model using a titanium cage coated with a PDLLA carrier including no growth factors, as well as with different concentrations of IGF-1 and TGF-beta-1. The authors concluded that the application of IGF-1 and TGF-beta-1 by a PDLLA-coated cage significantly improves interbody bone formation in a dose dependent manner, as assessed via micro-CT and histomorphometrical analysis, at 12 wk postoperatively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Kandziora et al[45] investigated the effects of IGF-1/TGF-beta-1 in a sheep anterolateral (C3-C4) interbody model using a titanium cage coated with a PDLLA carrier including no growth factors, as well as with different concentrations of IGF-1 and TGF-beta-1. The authors concluded that the application of IGF-1 and TGF-beta-1 by a PDLLA-coated cage significantly improves interbody bone formation in a dose dependent manner, as assessed via micro-CT and histomorphometrical analysis, at 12 wk postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this heterogeneity, directly comparing end points ( i.e ., rates of fusion) across multiple studies is not possible. Further, three studies did not report fusion rates[36,38,45], limiting the interpretability of those studies. In addition, our review excludes growth factors that have been studied clinically in spinal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of growth factor used depends on the size of the implants, as the growth factors are administered in a specific w/w ratio to the poly(D,L-lactide) scaffold. The w/w ratio that we used was based on previous experience ( Kandziora et al 2003 , Lamberg et al 2006 ). It is possible that even better results would be obtained with different ratios, and this is the subject of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the accelerated healing is difficult to determine, as a variety of time points were not evaluated and the treated limbs did not approach intact biomechanical values. In addition, this combination was shown to enhance interbody spinal fusions when coated on titanium fusion cages [41][42][43]. FGF, delivered with a hyaluronan material, has also been evaluated in several preclinical models of fracture repair.…”
Section: Bone Tissue Engineering Using Growth Factorsmentioning
confidence: 99%